Optimization of a Continuous Preparation Method of Arthrospira platensis γ-linolenic acid by supercritical carbon dioxide technology using response surface methodology - Yao, Ching Hsueh; Be, Jen Wang; Zer, Ran Yu; Cheng, Chi Wang; Malcolm Koo (Universiti Kebangsaan Malaysia, 2015)
γ-linolenic acid is an essential omega-6 unsaturated fatty acid made in the human body from linoleic acid. It can be metabolized to various important eicosanoids and it is also a precursor of prostaglandin E and several other active substances that are associated with anti-inflammatory properties. Arthrospira platensis is known to contain relatively large quantities of γ-linolenic acid. The aim of this study was to investigate the optimal parameters under a continuous preparation method of γ-linolenic acid from A. platensis using supercritical carbon dioxide technology. A Box-Behnken experimental design and response surface methodology were used to optimize combinations among pressure (10, 20 and 30 MPa), temperature (40, 50 and 60°C) and flow rate of A. platensis extract liquor (1, 2 and 3 mL/min) for yield of γ-linolenic acid. The results showed that the extraction of γ-linolenic acid from A. platensis was optimized at a temperature of 60°C, a pressure of 30 MPa and a flow rate of 3 mL/min. These parameters could be used as a basis for facilitating future scale-up industrial applications.